Nanoparticles with solution-process for dielectric applications in organic thin-film transistors - Gan, Ye (2010)
The PhD thesis presented here mainly focuses on investigation of the solution process-fabricated dielectrics from organic-capped inorganic nanoparticles for high-performance organic TFTs. A series of solution-processable oleic acid (OA) capped titanium dioxide (TiO2), barium titanate (BTO), strontium titanate (STO), and barium strontium titanate (BST) hybrid nanoparticles were synthesized. The dielectric constant k of the OA capped nanoparticle films is tunable in the range of 4.1 to 9.5 by simply altering the composition and ratio of the inorganic core elements. Organic TFTs fabricated using the high-k dielectric material demonstrate low-voltage modulated high-performance. Fundamental studies suggest that the low-voltage operation of the transistors could be attributed to a low density of trapped states at the interfaces between the organic semiconductors and the nanoparticle dielectric films. The success of this work renders a universal approach to fabricate high-k nanoparticle dielectrics and may have potential applications in printable electronics.